Endogenous fibrinolytic potential in tissue-plasminogen activator-modified thromboelastography analysis is significantly decreased in dogs suffering from diseases predisposing to thrombosis - Spodsberg, Eva H (Veterinary clinical pathology, 2013)
© 2013 American Society for Veterinary Clinical Pathology.